Dietary Fiber-Rich Spartina anglica Improves Intestinal Health and Antioxidant Capacity of Zhedong White Geese - Xiao Zhou; Li Wang; Jiuli Dai; Huiyan Jia; Kai Shi; Jian Zhao; Shufang Chen (Antioxidants)
Spartina anglica (SA), a plant rich in dietary fiber, has demonstrated considerable potential for enhancing gut health and antioxidant capacity in animals. This study investigates the integration of SA as a novel dietary ingredient for Zhedong white geese, with a specific focus on evaluating its effects on growth performance, nutrient digestibility, antioxidant capacity, intestinal health, and cecal microbiota composition. A total of 360 1-day-old Zhedong white geese with an average weight of 114.94 ± 0.81 g were randomly allocated to 4 dietary treatments, with 6 replicates per treatment and 15 geese per pen. The 4 dietary treatments included different SA supplement levels: a control group receiving a basal diet (CON), and three experimental groups supplemented with 3% SA (SA3), 6% SA (SA6), and 12% SA (SA12). Supplementation with 6% SA significantly enhanced the final body weight, average daily gain, and feed conversion ratio (FCR) compared to the CON group (p < 0.05). In contrast, the SA12 group exhibited reduced digestibility of crude protein and ether extract, relative to the SA3 and SA6 groups (p < 0.05). The highest antioxidant capacity was observed in the SA6 and SA12 groups, while the lowest was recorded in the CON group. SA supplementation did not significantly influence serum biochemical parameters or organ indices but increased cecum length (p < 0.05). Notably, SA supplementation markedly improved intestinal morphology, although excessive levels appeared to compromise these benefits. Additionally, SA supplementation significantly enhanced the richness and diversity of cecal microbiota and increased short-chain fatty acid concentrations. In conclusion, SA at an optimal supplementation level of 6% may be effectively utilized in Zhedong white geese diets to improve growth performance, gut health, and antioxidant capacity.